Enabling people with dementia to access and receive cancer treatment and care: The crucial role of supportive networks. Issue 7 (September 2020) - Surr, Claire A.; Kelley, Rachael; Griffiths, Alys W.; Ashley, Laura; Cowdell, Fiona; Henry, Ann; Collinson, Michelle; Mason, Ellen; Farrin, Amanda J.
Abstract: Objectives: Despite cancer and dementia being conditions in which prevalence increases with age, there remains limited research on the cancer treatment and care needs of this population. Our study aimed to address this gap and this paper reports on the role of supportive networks in enabling people with dementia to access cancer treatment and care. Materials and methods: An ethnographic study involving seventeen people with cancer and dementia, 22 relatives and nineteen oncology staff. It comprised observations (46 h) of and informal conversations during oncology appointments attended by people with dementia and their relatives and semi-structured interviews ( n  = 37) with people living with cancer and dementia, their relatives and staff working in various roles across oncology services. Data were analysed using thematic analysis. Results: Patients and oncology staff relied on and expected relatives to provide practical and emotional support around cancer treatment and care. Families varied in their ability to provide required support due to extent of the family network, practical issues, knowledge of the patient and their wishes, family conflict and the patient's willingness to accept help. Where no family network was available, support provision was complex and this could compromise access to cancer treatment. Conclusions: People with comorbid cancer and dementia rely heavily on a supportive family network to access treatment and care. Oncology services need to assess the supportive networks available to individual patients in developing cancer treatment plans. Urgent consideration needs to be given to how those with no family networks can be appropriately supported. Highlights: Supportive networks are vital for people with dementia to access cancer treatment. Provision of such support by families is often expected by oncology staff. Some families have greater resources to provide support than others. Providing this support can lead to guilt, stress and worry. It is unclear who provides this support where there is no family network.